Math, asked by thatGuyWhoAsksStuff, 3 months ago

if cosec theta + cot theta = 1/2 then, cosec theta - cot theta = ?​

Answers

Answered by TrustedAnswerer19
51

Answer:

Given,

cosec \:  \theta \:  + cot \:  \theta \:  \:  =  \frac{1}{2}  \\ cosec \:  \theta \:  + cot \:  \theta \:  \:  =  \: to \:  \: find \\  \\ we \: know \: that \:  \\  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  {cosec}^{2}  \: \theta \:  -  {cot}^{2}  \: \theta \:  = 1 \\  \implies \: (cosec \: \theta \:  + cot \: \theta \: )(cosec \: \theta \:  - cot \: \theta \: ) = 1 \\  \implies \:  \frac{1}{2}  \times (cosec \: \theta \:  - cot \:  \theta \: ) = 1 \\  \implies \: (cosec \: \theta \:  - cot \:  \theta \: )  = 2

Similar questions